Trust and mistrust in fan relationship management: survey evidence on Russian football fans - Reichel, Kristoff; Sannikov, Ilia; Brandt, Christian; Kurscheidt, Markus (Frontiers in Sports and Active Living, 2025)
IntroductionTrust is a key factor in governance and business. This is notably the case in professional sports with the large stakeholder group of fans as they claim a more active role than consumers in other industries. Thus, they may influence sport policy directly or indirectly, positively or negatively, through their communication, self-organization, coordinated activism and behavior. Particularly in football, the relationship between fans and sport organizations has attracted the interest of researchers. However, empirical studies primarily focused on Western football leagues within liberal political and cultural environments. Trust and mistrust in institutions may be more important in state-regulated environments, such as in the Russian Federation. Therefore, this study investigates the level of trust and questions the formation of trust in sport governing bodies among Russian football fans.MethodsThis article presents evidence from the first large-scale survey of supporters of the Russian Premier League (N = 4,090) with a focus on fans' attitudes, behaviors, and concerns. It is based on a questionnaire covering relevant issues in football governance that had been applied in different environments before. Adapted to specificities of Russian football, in particular, an item battery on the construct of trust was added: “How much do you trust the following institutions with regard to the organization of football?” The survey was distributed online in September and October 2022 via more than fifteen Telegram channels. Due to the wide regional distribution of participants and high sample size, the dataset is considered approximately representative of active Russian football supporters who engage on social media. Ordered logit regressions of trust variables were performed on numerous explanatory variables of attitudes, behaviors, and sociodemographics.ResultsThe findings reveal that supporters express the greatest confidence in supporter organizations, followed by clubs, while trust in local football organizations, such as the league and the association, as well as in international bodies including UEFA and FIFA, tends to be more limited. The regression models on trust variables regarding the favorite club and the league governance confirm that good relations with the fans, all else equal, foster trust in the football organizations while disrespect for the needs and self-concept of fans lower trust. In contrast to Western European fans, Russian supporters value elements of commercialization as modernization and respond with higher trust levels. Yet, closer emotional attachment to their club makes fans more skeptical about the trustworthiness of football officials while the belief in reforms of Russian football strengthens trust in the governing bodies.DiscussionThe findings and insights from the survey clearly emphasize that clubs and league governing bodies should acknowledge fans' active role distinguishing them from ordinary customers. If football officials wish to strengthen fans' trust they should invest in fan relations. This is in line with evidence on Western European fans. However, the results in detail show distinct differences which underlines the need for more diverse evidence on fan attitudes worldwide. The institutional environments matter and deserve more attention in sports economics and management research.